Robot Assisted Radical Cystectomy Outcomes in Micropapillary and Plasmacytoid Variants: RARC in variant pathology - Koç, Erdem; Gök, Bahri; Gumuskaya, Berrak; Atmaca, Ali Fuat; Canda, Abdullah Erdem; Balbay, Mevlana Derya (Urology Journal, 2020)
Purpose: To compare the patients who underwent robot assisted radical cystectomy (RARC) and extended pelvic lymph node dissection (EPLND) and whose pathology result was reported as micropapillary variant (MV), plasmacytoid variant (PV) and pure urothelial carcinoma (PUC). Materials and Methods: The data of 133 patients who underwent RARC and EPLND with the postoperative pathology results reported as MV, PV and PUC were analyzed. According to the postoperative pathology results, patients were divided into two groups in initial analyses as variant pathologies group (n=14) and PUC group (n=119). In secondary analyses, patients were divided into three groups as MV group (n=7), PV group (n=7) and PUC group (n=119). The operative data, oncologic outcomes and complications were compared between the groups. Results: Median operation time and estimated blood loss were significantly increased in variant pathologies group (P <0.001 and P = .001, respectively). The postoperative pathological T stage, positive surgical margin rate and lymph node involvement were also significantly increased in variant pathologies (P = .001, P = 0.004, P <0.001, respectively). Kaplan-Meier analysis revealed significant decrease in OS and CSS times in PV group compared to PUC group (P = .048 and P = .016, respectively). Conclusion: MV and PV are rarely seen variant pathologies with higher pathological T stages. RARC is a minimally invasive surgical technique that can be performed successfully by an experienced surgical team with low morbidity rates and similar oncological results, even in challenging cases.